Legal Study Of Asset Confidentiality Without Punishment As An Alternative For Providing Justice For The State And Persons Of Corruption - Melky AS Mendrofa (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Confiscation of assets regulated in criminal acts of corruption is based on Article 18 paragraph (1) of Law Number 20 of 2001 concerning Eradication of Corruption Crimes. The form of asset confiscation without punishment as an alternative to providing justice for the state and perpetrators of criminal acts of corruption consists of an asset confiscation system using the Non Conviction Based Asset Forfeiture model and implementing the mandate of UNCAC as the State. The establishment of legal rules regarding confiscation of assets without punishment as an alternative to providing justice for the state and perpetrators of criminal acts of corruption in realizing a welfare state, at least taken in several progressive legal steps, namely improving statutory regulations, strengthening coordination between law enforcement agencies, and accelerating finalize the Asset Recovery Act.